Pathological Narcissism and Emotional Responses to Rejection: The Impact of Adult Attachment - Reis, Samantha; Huxley, Elizabeth; Eng Yong Feng, Bryan; Grenyer, Brin F. S. (Frontiers in Psychology, 2021)
Aspects of pathological narcissism, such as grandiosity, vulnerability and entitlement, tend be enacted in therapeutic settings, negatively influencing outcome and therapeutic alliance. This research aimed to understand the interplay between emotional reactions of individuals with a pathological narcissistic presentation and current attachment style. We predicted that participants reporting narcissistic vulnerability would report greater insecurity in attachment, greater trait emotional reactivity, and also experience more negative responses to rejection. 269 participants (75.84% female, median age = 21) completed baseline and rejection trials of a virtual ball-tossing game, following the assessment of grandiose and vulnerable pathological narcissism, entitlement, adult attachment, trait emotional reactivity (measured prior to the rejection) and affective response (measured before and after the rejection). Vulnerable narcissism was positively associated with fearful and preoccupied attachment, and negatively associated with secure and dismissive attachment, whilst grandiose narcissism was significantly related to preoccupied attachment. Multiple hierarchical regression analyses showed vulnerable narcissism predicted a) negative trait emotional reactivity and b) significant increases in negative affect following rejection. Grandiose narcissism was associated with a) positive trait emotional reactivity, and b) significant reductions in positive affect following rejection. Conclusions: Results indicated that those high in pathological narcissistic vulnerability reported greater insecurity in attachment, negative trait emotional reactivity and experienced a more negative emotional reaction to rejection. Grandiose narcissism was related to a more deactivated pattern of emotional reactivity, and less positive (rather than more negative) emotional reactions. Findings have implications for therapy, particularly regarding communication of emotions for individuals high in vulnerable and grandiose narcissism.